How Boston Played : Sport, Recreation, and Community, 1865-1915 - Hardy, Stephen, 1948- (Book collections on Project MUSE., 2019)
How Boston Played is a double delight. It chronicles the birth of Boston sports from early Redstockings games and college rowing regattas, to the exploits of the "Boston Strong Boy," John L. Sullivan. Looking beyond just sporting events, though, it seeks to uncover the sources of the mania for recreation that swept the Hub following the Civil War. As How Boston Played illustrates, the rise of sport is firmly entwined in both the city's development and, more importantly, in a people's search for community. Originally published by Northeastern University Press in 1982. With a new foreword by Mark Herlihy.